2010
DOI: 10.2214/ajr.09.3484
|View full text |Cite
|
Sign up to set email alerts
|

Apparent Diffusion Coefficient of Fibrosis and Regenerative Nodules in the Cirrhotic Liver at MRI

Abstract: The mean ADC of fibrosis is significantly greater than that of regenerative nodules both in vivo and ex vivo. The prevailing paradigm that fibrosis causes the reduced liver ADC observed in cirrhosis may need modification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Previous studies demonstrated that ADC of liver tissue gradually decreases as hepatic fibrosis progresses (21, 22). Recently, Mwangi et al (23) measured and compared the ADC values of fibrous components and regenerative nodules through ex vivo and in vivo studies of cirrhotic livers. They demonstrated that the mean ADC value of fibrotic components was significantly greater than that of regenerative nodules or background cirrhotic liver parenchyma.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies demonstrated that ADC of liver tissue gradually decreases as hepatic fibrosis progresses (21, 22). Recently, Mwangi et al (23) measured and compared the ADC values of fibrous components and regenerative nodules through ex vivo and in vivo studies of cirrhotic livers. They demonstrated that the mean ADC value of fibrotic components was significantly greater than that of regenerative nodules or background cirrhotic liver parenchyma.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study indicates that fibrotic tissue and RNs have unique diffusion properties and that, contrary to the prevailing paradigm, diffusion is more restricted in RNs than in fibrosis. The lower ADC in RNs compared with ADC in fibrotic bridges may be explained by microscopic structural differences between the two tissues [20].…”
Section: Cirrhosismentioning
confidence: 99%
“…In this study, we compare IVIM parameters derived from the BLN error model with those derived from the LS error model. Direct assessment of the accuracy of parameters derived from each model is not possible, since perfusion does not occur in ex vivo liver phantoms that could otherwise be used as gold standard reference values . However, the effects of bulk motion vary across the cardiac and respiratory cycles and across the liver.…”
mentioning
confidence: 99%